Maternal dietary intake of choline in mice regulates development of the cerebral cortex in the offspring. Issue 4 (23rd December 2015) - Wang, Yanyan; Surzenko, Natalia; Friday, Walter B.; Zeisel, Steven H.
Abstract : Maternal diets low in choline, an essential nutrient, increase the risk of neural tube defects and lead to low performance on cognitive tests in children. However, the consequences of maternal dietary choline deficiency for the development and structural organization of the cerebral cortex remain unknown. In this study, we fed mouse dams either control (CT) or low‐choline (LC) diets and investigated the effects of choline on cortical development in the offspring. As a result of a low choline supply between embryonic day (E) 11 and E17 of gestation, the number of 2 types of cortical neural progenitor cells (NPCs)—radial glial cells and intermediate progenitor cells—was reduced in fetal brains ( P < 0.01). Furthermore, the number of upper layer cortical neurons was decreased in the offspring of dams fed an LC diet at both E17 ( P < 0.001) and 4 mo of age ( P < 0.001). These effects of LC maternal diet were mediated by a decrease in epidermal growth factor receptor (EGFR) signaling in NPCs related to the disruption of EGFR posttranscriptional regulation. Our findings describe a novel mechanism whereby low maternal dietary intake of choline alters brain development.—Wang, Y., Surzenko, N., Friday, W. B., Zeisel, S. H. Maternal dietary intake of choline in mice regulates development of the cerebral cortex in the offspring. FASEB J. 30, 1566–1578 (2016). www.fasebj.org